Coumarin-based thiosemicarbazones as potent urease inhibitors: synthesis, solid state self-assembly and molecular docking. Issue 68 (5th July 2016) - Hameed, Aminah; Yaqub, Muhammad; Hussain, Mazhar; Hameed, Abdul; Ashraf, Muhammad; Asghar, Humna; Quart-ul-Ain,; Naseer, Muhammad Moazzam; Mahmood, Khalid; Muddassar, Muhammad; Tahir, Muhammad Nawaz; Shafiq, Zahid
Abstract : A series of coumarin-based thiosemicarbazones and their metal complexes have been synthesized and their in vitro potency against urease was evaluated. Abstract : A series of coumarin-based thiosemicarbazones and their metal complexes have been synthesized and their in vitro potency against urease was evaluated. Single crystal X-ray crystallographic studies were carried out for compound14 to investigate the solid state self-assembly which showed a preference for the S -conformation owing to intramolecular hydrogen bonding. An in vitro urease inhibition assay revealed coumarin-thiosemicarbazone12 as the most potent inhibitor (IC50 value of 2.23 ± 0.14 μM) compared to thiourea, used as standard (IC50 value of 21.25 ± 0.15 μM). Similarly, compounds4, 6, 7, 9, 15 &16 showed excellent urease inhibition activity with IC50 values ranging from 4.15 ± 0.17 to 16.95 ± 0.12 μM. Furthermore, compounds3, 8, 11 &13 also showed good activities (IC50 values ranging from 33.86 ± 0.12 to 43.12 ± 0.19 μM) against this enzyme. However, the metal complexes of these compounds showed low activity against urease. Molecular docking with the most cogent ligand against urease was also performed to assess the putative binding mode of the synthesized compounds. Potent compound12 can serve as a potential lead for further chemical tuning towards drug candidate development.